2013
DOI: 10.1159/000355223
|View full text |Cite
|
Sign up to set email alerts
|

After the Introduction into the National Newborn Screening Program: Who Is Receiving Genetic Counseling for Hemoglobinopathies in The Netherlands?

Abstract: Objective: Universal newborn screening for hemoglobinopathies started in The Netherlands in 2007. Herewith severe conditions, such as sickle cell disease, β-thalassemia major and hemoglobin H disease are putatively identified. Additionally, at least 1,800 carriers of hemoglobin variants associated with severe conditions in homozygote or compound heterozygote forms are identified yearly. Thus far, approximately 60 patients and 800 healthy sickle cell (HbS) carriers are reported each year among 180,000 newborns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The reasons can be searched in the partial report of carriers (HbS only), in the possibly directive counseling if focused on treatment rather than on explaining the severity of the progressive diseases, in the lack of motivation of part of the badly informed target population [29] and last but not least in potential conflict of interests that, as suggested by Kabbak, could be felt in some systems, as conflicts of interest on the part of entrepreneurial scientists vs . clinicians, and institutions [8].…”
Section: Hemoglobinopathiesmentioning
confidence: 99%
“…The reasons can be searched in the partial report of carriers (HbS only), in the possibly directive counseling if focused on treatment rather than on explaining the severity of the progressive diseases, in the lack of motivation of part of the badly informed target population [29] and last but not least in potential conflict of interests that, as suggested by Kabbak, could be felt in some systems, as conflicts of interest on the part of entrepreneurial scientists vs . clinicians, and institutions [8].…”
Section: Hemoglobinopathiesmentioning
confidence: 99%
“…Most of the developed countries have NBS programs in place which can screen for different inherited disorders at the time of birth or soon after birth (1116). However, sadly, there is still no local or national level NBS program for any of the IEM in Pakistan—a country with population of more than 220 million.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the identification of children with a HbP, carrier status can be reported from neonatal screening as well. In that case parents may be referred to genetic centers for counseling, especially carrier couples, though it has been shown that few couples in the Netherlands are seen in genetic centers (Kaufmann et al 2014 ). Screening offers also differ in the way of delivery (universal or ancestry-based), the timing (premarital, preconceptional or prenatal), its mandatory or voluntary character, and counseling and informed consent procedures (Cousens et al 2014 ; Cousens et al 2010 ; Giordano et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%